Effectiveness of Cognitive Counseling Modeling Technique Through Lesson Study to Improve Resolving Something Behavior self achievment Class X SMK Negeri 2 Singaraja - Yulianingtyas Rahmawati; I Ketut Dharsana; Ni KetutSuarni (International Conference on Technology and Educational Science)
This study aims to determine the effect of cognitive counseling with modeling techniques to improve the self achievement of students and differences in behavior adjust something well and will succeed. The population of this study population was 64 student with a sample of 32 students. This type of research is quasi experiment, with pretest and posttest control group design.The method of collecting data uses a behavioral question are to get things done well snd will succeed in 30 items. Result of data analysis thit9,86 >ttab1.724, so thare are significant differences. It can be concluded that cognitive counceling modeling techniques through lesson study effectively improve the behavior of completing things well and will succeed in class X SMK N 2 Singaraja